PENGEMBANGAN APLIKASI SUPERVISI AKADEMIK BERBASIS WEBSITE UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU MTS - Rufaida, Diena; Kusumaningsih , Widya; Ginting , Rosalina Br (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
The implementation of academic supervision of teachers at MTs in Subah District still faces several obstacles. Initial observations show that academic supervision is still carried out manually, making it less efficient and not well documented. In addition, limited time and resources cause the supervision process to not be carried out optimally. As a result, many teachers do not get constructive feedback to improve the quality of their learning. So the author developed a website-based academic supervision application to improve the effectiveness of academic supervision. The hope of developing this website-based academic supervision application is that it can improve teacher pedagogical competence and improve the quality of academic supervision of MTs teachers in Subah District. This study uses the Research and Development method, with the Borg and Gall model that has been modified by Sugiyono. Data collection techniques using interviews, questionnaires and observations. Data validity testing uses data source triangulation. The development stage involves experts and practitioners. The validity stage is carried out with a validation questionnaire from media experts and material experts, field trials, and effectiveness analysis to determine the effectiveness of developing a website-based academic supervision application. The results of the study on the analysis of the effectiveness of the development of this website-based academic supervision application can be seen in the field trial involving 25 teachers in three MTs in Subah District, obtained a total score of 1,782 with a maximum score of 2,000 so that an effectiveness value of 89.1% was obtained with a very effective category. This shows that the development of a website-based academic supervision application is effective and feasible to be implemented in MTs in Subah District. ABSTRAKPelaksanaan supervisi akademik guru di MTs Kecamatan Subah masih menghadapi beberapa kendala. Observasi awal menunjukkan bahwa supervisi akademik masih dilakukan secara manual, sehingga kurang efisien dan tidak terdokumentasi dengan baik. Selain itu, keterbatasan waktu dan sumber daya menyebabkan proses supervisi tidak dapat dilakukan secara optimal. Akibatnya, banyak guru yang tidak mendapatkan umpan balik yang konstruktif untuk meningkatkan kualitas pembelajaran mereka. Sehingga penulis mengembangkan sebuah aplikasi supervisi akademik berbasis website untuk meningkatkan efektifitas supervisi akademik. Harapan dari pengembangan aplikasi supervisi akademik berbasis website ini dapat meningkatkan kompetensi pedagogik guru dan meningkatkan kualitas supervisi akademik guru MTs di Kecamatan Subah. Penelitian ini menggunakan metode Research and Development, dengan model Borg and Gall yang telah di modifikasi oleh Sugiyono. Teknik pengumpulan data dengan cara wawancara, angket dan observasi. Uji keabsahan data menggunakan triangulasi sumber data. Tahap pengembangan melibatkan ahli dan praktisi. Tahap validitas dilakukan dengan angket validasi ahli media dan ahli materi, ujicoba lapangan, serta analisis efektifitas untuk mengetahui efektifitas pengembangan aplikasi supervisi akademik berbasis website. Hasil penelitian pada analisis efektifitas pengembangan aplikasi supervisi akademik berbasis website ini, dapat terlihat pada ujicoba lapangan yang melibatkan 25 guru di tiga MTs Kecamatan Subah diperoleh jumlah skor 1.782 dengan skor maksimal 2.000 sehingga diperoleh nilai efektifitas sebesar 89,1% dengan kategori sangat efektif. Hal ini menunjukkan bahwa pengembangan aplikasi supervisi akademik berbasis website efektif dan layak diterapkan di MTs Kecamatan Subah.